2013
DOI: 10.5688/ajpe77359
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Simulation for Advanced Cardiac Life Support Training

Abstract: Objective. To determine whether a high-fidelity simulation technique compared with lecture would produce greater improvement in advanced cardiac life support (ACLS) knowledge, confidence, and overall satisfaction with the training method. Design. This sequential, parallel-group, crossover trial randomized students into 2 groups distinguished by the sequence of teaching technique delivered for ACLS instruction (ie, classroom lecture vs high-fidelity simulation exercise). Assessment. Test scores on a written exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 15 publications
1
58
0
1
Order By: Relevance
“…5 The majority of this evidence includes the use of highfidelity mannequin simulation instruction. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A number of outcomes (eg, self-perceived clinical skills, teamwork and interprofessional teamwork skills, blood pressure assessment) have been assessed using high-fidelity mannequins. Although it has been shown that high-fidelity mannequin simulation can increase knowledge retention in pharmacy education, data is lacking on retention of advanced cardiac life support (ACLS) knowledge and skills following simulation training.…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of this evidence includes the use of highfidelity mannequin simulation instruction. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A number of outcomes (eg, self-perceived clinical skills, teamwork and interprofessional teamwork skills, blood pressure assessment) have been assessed using high-fidelity mannequins. Although it has been shown that high-fidelity mannequin simulation can increase knowledge retention in pharmacy education, data is lacking on retention of advanced cardiac life support (ACLS) knowledge and skills following simulation training.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the simulation experience did not improve students' knowledge more than attending lectures; however, it did improve students' confidence in their skills, as well as satisfaction with learning. 10 It was recommended that future curricula incorporate simulation as a complement to lecture learning in ACLS education. 10 This supports the use of HFMS in athletic therapy education as it allows students to ''experience'' catastrophic injury scenarios in a safe environment and gain essential confidence without real-world consequences.…”
Section: Discussionmentioning
confidence: 99%
“…10 It was recommended that future curricula incorporate simulation as a complement to lecture learning in ACLS education. 10 This supports the use of HFMS in athletic therapy education as it allows students to ''experience'' catastrophic injury scenarios in a safe environment and gain essential confidence without real-world consequences. It also exposes students to injuries and conditions that they may not encounter during their education tenure, giving them the necessary skills and experience to begin their career with confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az oktatás módszere is nagy hatással van a megszerzett ismeretekre, amely során a gyakorlati résznek hangsúlyosnak kell lennie. Az American Heart Association (AHA) által végzett kutatásban kimutatták, hogy a legjobb eredmény akkor volt elérhető, amikor a hagyományos elméleti oktatást valósághű szimulációs gyakorlattal egészítették ki [14]. A Wik és mtsai által végzett kutatás azt mutatta ki, hogy az általuk vizsgált prehospitális szakellátók által végzett újraélesztés minősége elmarad az elvárt szinttől [15].…”
unclassified